Adjustment of laser scattering focus with machine learning. (12th July 2018) - Haoyi, Zuo; Zuogang, Yang; Longjie, Fang; Shirong, Luo
Abstract: The adjustment of the intensity of laser scattering focus with machine learning based on the back propagation (BP) neural network is proposed in this paper. Focus based on 'laser scattering' is more flexible than that based on a lens and imaging based on 'laser scattering focus' can break through the diffraction limit of lens imagingin order to obtain higher resolution. Therefore, knowing how to adjust the scattering focus is very important. In this paper, we used known data to train a BP network, and then used the trained BP network to realize the rapid and arbitrary adjustment of the intensity of the scattering focus. This method has potential application value in the field of 'laser scattering focus'. In addition, with the rapid development of artificial intelligence, machine learning is increasingly being used in various fields, including physics. We hope that machine learning can also be applied to 'laser scattering focus'. Therefore, in this paper, we conducted some preliminary investigations, which could provide reference for further research.